School Principal Leadership Strategy in Multicultural Islamic Education Towards Forming Student’s Al-Musawah and Al-Rahmah Attitudes at SMP Negeri 15 Surabaya: Strategi Kepemimpinan Kepala Sekolah Dalam Pendidikan Islam Multikultural Terhadap Pembentukan Sikap Al-Musawah Dan Al-Rahmah Peserta Didik di SMP Negeri 15 Surabaya - Hermawan, Didik; Hariyanto, Didik (Indonesian Journal of Innovation Studies, 2026)
General Background: Education in a disruptive era must serve as a medium to cultivate positive attitudes toward social and religious diversity. Specific Background: In multicultural school settings, implementing structured leadership strategies is critical to managing student diversity and building social cohesion. Knowledge Gap: However, practical strategies for embedding specific ethical values like Al-Musawah (equality) and Al-Rahmah (affection) into concrete school programs remain insufficiently detailed in secondary education contexts. Aims: This qualitative case study evaluates the principal’s leadership strategies in implementing multicultural Islamic education to foster Al-Musawah and Al-Rahmah attitudes among students at SMP Negeri 15 Surabaya. Results: Findings reveal that the principal implemented all-inclusive policies through structured programs, including peer counselors, P5 global diversity projects, and the Jumat Berkah Better community. Novelty: The research highlights a framework integrating religious ethics into non-discriminatory, student-led extracurricular and curricular social actions. Implications: These strategies effectively eliminate religious discrimination, intensify positive cross-cultural student interactions, and increase self-confidence among minority students. Key Findings Highlights Structured leadership strategies enable the integration of Al-Musawah and Al-Rahmah values through all-inclusive school policies. Peer counseling, P5 global diversity initiatives, and community service projects foster empathy and cross-cultural student engagement. All-inclusive school environments prevent religious discrimination while boosting the self-confidence of minority students. Keywords: School Principal Leadership, Multicultural Education, Student Attitude Formation, Inclusive School Policy, Diversity Management